The philosophical idea of peace: the formation and evolution - Panafidin, Igor (Actual Problems of Mind, 2017)
The paper investigates an evolution of the idea of eternal peace from philosophico-mythological views onwards and up to its classical formulation by Kant. The author claims a factual realization of the theory of eternal peace in a Kantian sense implying a peaceful coexistence of people by establishing a federation of states on the principles of parity and justice.